Nigeria’s 1969 Curriculum Conference: a practical approach to educational emancipation - Akanbi, Grace Oluremilekun; Abiolu, Oluremi Adenike (Cadernos de História da Educação, 2018)
After Nigeria got her independence on 1 October, 1960, the general consensus was that there was the need for educational emancipation through decolonization of the academic contents of education; to make education relevant to the needs of the individual and the society at large. This led to the organisation of the 1969 Curriculum Conference which had far-reaching effects on the curriculum contents, purposes, goals and objectives of education in Nigeria. However, what obtains in the education sector today makes it to look as if there was no initial proper planning for educational emancipation. This paper, therefore, focuses Nigeria’s 1969 Curriculum Conference (CC) as a practical approach to educational emancipation in Nigeria. In the conceptual framework of the globalisation of education, Cookey’s (1972: xxv) observation during the conference that, "education then tends to produce children who can read and write and pass examinations and which qualify them for employment only as clerks" was an important reason for the conference and is still relevant today as a major issue for discussion in our education outcomes. This study is historical; it, therefore, employs the historical method to collect information and facts needed through both primary and secondary sources. As the study recommends among others that there is the need for total overhauling of Nigerian educational policies and philosophy, it is hoped that the research would sensitise all stakeholders in Nigeria to emphasise the importance of providing a functional educational curricula relevant to the needs of individuals and the society at large. Keywords: Curriculum Conference, Emancipation, National Policy on Education, Decolonisation. Resumo Após a Nigéria conseguir sua independência em 1 de outubro, 1960, o consenso geral era que havia a necessidade da emancipação educative por meio da descolonização dos conteúdos acadêmicos de educação; para tornar a educação relevante às necessidades do indivíduo e da sociedade em geral. Isso levou Ã organização da Conferência Curricular de 1969 que teve efeitos extensos nos conteúdos curriculares, propósitos, metas e objetivos de educação na Nigéria. No entanto, o que se obtêm no setor de educação hoje faz parecer que não havia planejamento inicial adequado para emancipação educacional. Este artigo, portanto, foca na Conferência Curricular de 1969 da Nigéria (CC) como uma abordagem prática para a emancipação educativa na Nigéria. Na estrutura conceitual da globalização da educação, a observação de Cookey (1972: xxv) durante a conferencia que, "educação então tende a produzir crianças que podem ler e escrever e passar exames e que as qualificam para emprego apenas como escriturários" foi uma importante razão para a conferência e ainda é relevante hoje em dia como uma questão principal de discussão nos resultados da nossa educação. Este é um estudo histórico; ele, portanto, emprega o método histórico de coleta de informações e fatos necessários tanto por fontes primárias quanto secundárias. Como o estudo recomenda inclusive que há uma necessidade por total revisão das políticas e filosofia educacionais da Nigéria, é esperado que a pesquisa possa sensibilizar todas as partes interessadas na Nigéria em enfatizar a importância de prover um currículo de educação funcional relevante às necessidades dos indivíduos e da sociedade em geral. Palavras-chave: Conferência curricular, Emancipação, Política Nacional de Educação, Descolonização. Resumen Después de que Nigeria obtuvo su independencia el 1 de octubre de 1960, el consenso general consistía en que era necesaria la emancipación educativa a través de la descolonización de los contenidos académicos de la educación, hacer que la educación fuera relevante para las necesidades del individuo y de la sociedad en general. Esto condujo a la organización de la Conferencia Curricular de 1969, que tuvo efectos de gran alcance en los contenidos, propósitos, metas y objetivos de la educación en Nigeria. Sin embargo, lo que se obtiene hoy en el sector de la educación hace que considere que no hubo una planificación inicial adecuada para la emancipación educativa. Este documento, por lo tanto, se enfoca en la Conferencia Curricular de 1969 (CC) de Nigeria como un enfoque práctico para la emancipación educativa en Nigeria. En el marco conceptual de la globalización de la educación, la observación de Cookey (1972: xxv) durante la conferencia refiriéndose a que "la educación tiende a producir niños que pueden leer y escribir y aprobar exámenes y calificándolos para el empleo solo como empleados", era un motivo importante de la conferencia, continuando relevante hoy como un importante tema para el debate en nuestros resultados educativos. Este es un estudio histórico; por lo tanto, emplea el método histórico para recopilar información y hechos necesarios a través de fuentes primarias y secundarias. Como el estudio recomienda, entre otros, la necesidad de una revisión total de las políticas y la filosofía educativas nigerianas, se espera que la investigación sensibilice a todas las partes interesadas en Nigeria para enfatizar la importancia de proporcionar un currículo educativo funcional relevante para las necesidades de las personas y la sociedad en general. Palabras clave: Conferencia Curricular. Emancipación. Política Nacional de Educación. Descolonización.